Chandraprabha Vati – A Formulation For Mootrakrichhra – A Literary Review - Charkha, Varad; Sharma, Shivani; Meena, Mohar Pal; Sharma, Reetu (International Research Journal of Ayurveda & Yoga, 2020)
Mootrakrichhra is a disease of Mootravaha Srotas and mentioned in all main Ayurvedic texts. Mootrakricchra is a Tridoshaj Vyadhi and its symptoms are compared with Urinary tract infections (UTI) in modern texts. Main symptoms of Mootrakrichhra are pain and difficulty in micturition. Various formulations have been mentioned in ayurvedic texts for the treatment of Mootrakricchra. One of those formulations is Chandraprabha vati. Chandraprabha vati is a herbo-mineral preparation having 37 drugs. Though the efficacy of Chandraprabha vati in the above-mentioned condition is observed practically, its mode of action is not clear. In this article we have attempted to throw a light on a probable mode of action of Chandraprabha vati in Mootrakrichhra. Ingredients of Chandraprabha vati possess properties such as mutrala, deepana-pachana, tridoshaghna, sheeta virya and rasayana. Samprapti (pathophysiology) of Mootrakrichhra can be broken down by these properties. Experimental studies have proven the antioxidant & antimicrobial action of Chandraprabha vati. Thus, it stands as a formulation of choice in treatment of Mootrakricchra.